KESIAPAN INSTANSI PEMERINTAH DALAM IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL - Margareta, Weda Ayu; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to evaluate how far the readiness of the Secretariat of the Council of Regional Representatives (DPRD) of East Java Province in the implementation of accrual based government accounting standard (SAP). This research is descriptive research that has been carried out by using qualitative approach. The data collection method has been done by using interview technique and documentation. The result of the research shows that the staff of financial department of the Secretariat of the Council of Regional Representatives (DPRD) is quite ready in implementing the accrual government accounting standard (SAP), this has been proven by the staffs of financial department of the Secretariat of the Council of Regional Representatives (DPRD) who have been done all necessary preparations. The form of preparation is carried out by joining technical training or training from the Financial Management Agency of Local Assets (BPKAD), and by joining many kinds of workshops that are related to the implementation of accrual based government accounting standard (SAP).Keywords: Government Accounting Standard, Accrual Based, the Readiness of Government Institution.